Cognitive Control at Age 3: Evaluating Executive Functions in an Equitable Montessori Preschool - Phillips-Silver, Jessica; Daza, María Teresa (Frontiers in Education, 2018)
Studies in cognitive neuroscience have shown that education practices can affect the development of executive functions (EF) in young children, although there is very little evidence on young preschool children. The present study aims to provide support for this endeavor, and consists of a quasi-experimental design with one-group pre-test/post-test measures of cognitive control at age 3 in an urban public Montessori preschool. Three-year-olds (N=23) in an authentic Montessori public preschool in Washington DC improved significantly on core EF measures (inhibitory control and cognitive flexibility) validated by the NIH Toolbox Early Childhood Cognition Battery, and the data revealed large effect sizes. Comparisons against NIH published norms revealed no selection bias. Performance on EF measures did not correlate with age but did correlate with amount of time between testing sessions, suggesting the possibility that experience, more than age, could have contributed to cognitive control growth. A controlled comparison between mixed-age and single-age classes revealed no differences in these EFs, raising the possibility that aspects of the environment other than the age composition are likely to contribute to growth. We propose that a potential contributor to EF growth in Montessori education might be found in the design of interaction of the child with the environment—in particular, we discuss the design element called control of error, and consider why this element might be related to cognitive abilities such as inhibitory control. In current national discussions on the importance of equitable early childhood education, the synthesis of findings from neurocognitive studies has implications for children’s academic and life success.